Letters to the Editor - Anthony S. Blinkhorn, BDS, MSc, PhD (Blackwell Synergy, 2001)
recent guest editorial (1) in the Journal of Public Health Dentistry entitled "Qualitative Research-Does It Have a Place in Dental Public Health?" revisited the field of qualitative research. Under the hegemony of quantitative scientific methodology, this editorial serves nicely as a flagship in theJPHD for qualitative research to be recognized, discussed, and critiqued just as its quantitative counterpart.